Problems faced by local franchisees in running their business: a study of franchisees in Selangor / Hana Harlina Mohamed Abdullah - Mohamed Abdullah, Hana Harlina (Faculty of Business and Management, 2010)
This study was conducted among local franchisees from various franchise sectors like food, service and maintenance, nursery, beauty centre, etc. around Selangor district amongst others Klang Valley, Ampang, Cheras, Kajang, Bangi and many more. The purpose of the study is to study the problems faced by local franchisees in running their franchise business and to identify possible solutions for the unresolved conflicts between the franchisor and the franchisees. All information were obtained through observation, informal interviews and other secondary data from journals, newspaper and online articles. The study identified four main issues relating to the problems faced by local franchisees, amongst others, lack of effective communication and communication techniques, limited creativity and decision making, franchise fees and royalty and also franchisor’s frustration. Through observation, the researcher found that franchisees have unresolved conflicts with their franchisors but did not make them known to the franchisors for resolution. At the end of the study, the researcher offers few recommendations for future study that include encouraging dual communication between franchisor and franchisee, to appoint franchise consultant and last but not least to view the franchisee as an intelligent agent.